#### Answer

6a$^2$-23ab+20b$^2$

#### Work Step by Step

(3a-4b)(2a-5b)
=6a$^2$-15ab-8ab+20b$^2$
=6a$^2$-23ab+20b$^2$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

6a$^2$-23ab+20b$^2$

(3a-4b)(2a-5b)
=6a$^2$-15ab-8ab+20b$^2$
=6a$^2$-23ab+20b$^2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.